Changes in Glycolytic Pathway in SARS-COV 2 Infection and Their Importance in Understanding the Severity of COVID-19 - Santos, Adalberto Fernandes; Póvoa, Pedro; Paixão, Paulo; Mendonça, António; Taborda-Barata, Luís (Frontiers in Chemistry, 2021)
COVID-19 is an infectious disease caused by SARS-CoV-2, a coronavirus that, in a proportion of cases, can be severe, involving an acute respiratory syndrome and multiple organ failure. A probable excessive activation of the innate immune system and the need for viral replication in several cells of the infected organism, promote significant changes in the metabolism of cellular energy (glucose metabolism), which can be the basis of the poor prognosis of the disease in severe situations. Cells of the innate immune system reprogram their metabolism, when activated, and increase glucose uptake to ensure the secretion of pro-inflammatory cytokines. On the other hand, some cells of the innate system are infected by SARS-CoV 2, thereby compromising the synthesis of antiviral molecules. Changes in glucose metabolism are also observed in pulmonary epithelial cells, thereby contributing to dysregulation of epithelial-derived cytokine synthesis and inflammation in the lungs. Furthermore, both activated and/or infected T cells have impaired metabolic reprogramming in COVID-19, a scenario that facilitates viral replication and worsening inflammation in critically ill patients with the disease. Persistent inflammation promoted by dysregulation of immune cells, as well as deficiency in the production of type 1 IFN, also promoted by changes in glycolytic pathways, may contribute towards T-cell depletion observed in more severe COVID-19 cases. Understanding the changes in the glycolytic pathway associated with COVID-19 can help to find new forms of treatment for this disease.